Freelance Auditors on Responsibility, Independence, Risk and Objectivity: A Literature Review on the Practice of Public Accounting Firms in Indonesia - Danny Wibowo; Tanbir Hossain (Politeknik Siber Cerdika Internasional, 2026)
Background: The growing demand for audit services in Indonesia has led many Public Accounting Firms (Kantor Akuntan Publik [KAP]) to utilize freelance auditors as a flexible solution to address auditor shortages, particularly during peak audit seasons. With only 1,646 registered public accountants serving a population of 284.4 million (a ratio of 1:172,880), this practice has become widespread despite significant unresolved questions regarding legal responsibility, independence, and audit quality. While PMK 186/PMK.01/2021 and Law No. 5/2011 require all audit services to be conducted through KAPs, these regulations do not explicitly prohibit the use of freelance auditors, thereby creating a regulatory gray area with serious professional and ethical implications. Objective: This study examines the implications of using freelance auditors on legal responsibility, independence, professional risk, objectivity, and audit quality in Indonesian KAP practice. Methods: A qualitative Systematic Literature Review (SLR) was conducted, synthesizing academic articles from Scopus-indexed Q1/Q2 journals, Sinta 1/2 national journals, and professional auditing standards (ISA 220 Revised, ISQM 1, ISA 620, and the IESBA Code of Ethics 2024), selected from the 2014–2025 period. Results: Self-interest and familiarity threats were found to be the most prevalent among freelance auditors, driven by economic dependence on short-term assignments and the absence of structural independence controls. The complexity of the nine-dimensional agency relationship significantly increases moral hazard risk and weakens professional skepticism when adequate safeguards are absent. Conclusion: KAPs must strengthen quality management, supervision, documentation, and independence-testing systems to ensure that freelance labor does not degrade audit quality or increase litigation risk.